2012
DOI: 10.5511/plantbiotechnology.12.0319a
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the plastid transformation protocol by modifying tissue treatment at pre- and post-bombardment in tobacco

Abstract: Plastid transformation in higher plants has been established in tobacco using particle bombardment, and the protocol has been used as a model in other plant species; however, as target materials, tobacco leaves may be partially exposed to unexpected abiotic stresses-drought stress during post-bombardment culture and damage due to cutting before selection culture. Plastid transformation e ciency may be increased by modi cation of leaf treatment to lessen such damage. In the modi ed protocol, tobacco leaves were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
(19 reference statements)
1
12
0
Order By: Relevance
“…Kausch et al (1995) reported that DNA/gold particles formed extremely loose aggregates and were finely dispersed compared with tungsten particles. In our previous report, the DNA/gold solution with 0.6-µm gold particles was easily suspended by pipetting and low vortexing (Okuzaki and Tabei 2012). However, in our examination of DNA coating of small gold particles, the particles with aggregated DNA, and the aggregate could not be resuspended by pipetting and vortexing (data not shown).…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Kausch et al (1995) reported that DNA/gold particles formed extremely loose aggregates and were finely dispersed compared with tungsten particles. In our previous report, the DNA/gold solution with 0.6-µm gold particles was easily suspended by pipetting and low vortexing (Okuzaki and Tabei 2012). However, in our examination of DNA coating of small gold particles, the particles with aggregated DNA, and the aggregate could not be resuspended by pipetting and vortexing (data not shown).…”
Section: Discussionmentioning
confidence: 56%
“…The DNA/gold mixtures (10 µl) were applied onto a macrocarrier, dried, and bombarded on a sample plate containing 50 pieces of tobacco leaf (5×5 mm) as described by Okuzaki and Tabei (2012). Two shots per plate were performed using a 1100-psi (7.6 MPa) or 1350-psi (9.3 MPa) rupture disc under partial vacuum (711 mmHg) in a PDS-1000/He system (Bio-Rad Laboratories).…”
Section: Plastid Transformationmentioning
confidence: 99%
See 3 more Smart Citations